Ethnic Differences in Barriers and Enablers to Physical Activity Among Older Adults - You, Emily; Lautenschlager, Nicola T.; Wan, Ching Shan; Goh, Anita M. Y.; Curran, Eleanor; Chong, Terence W. H.; Anstey, Kaarin J.; Hanna, Fahad; Ellis, Kathryn A. (Frontiers in Public Health, 2021)
Despite its well-known health benefits, most older adults do not commit to undertaking sufficient physical activity (PA). In this study we aimed to examine the perceived benefits of and barriers and enablers to PA from the perspectives of older Caucasian and Chinese adults living in Australia. Individual and group interviews with 17 Caucasian (mean age: 72.8 years) and 47 Chinese adults (mean age: 74.0 years) were conducted and analysed using thematic analysis. Overall, participants knew about the benefits of PA on physical health but had inconsistent views on its benefits on mental and cognitive health. Older Caucasian and Chinese adults reported similar barriers (e.g., health issues, costs, bad weather and lack of time) and enablers (e.g., improving health; environmental enablers such as adequate and walkable spaces and good natural environment; peer support; and self-motivation) to PA. In comparison, older Chinese adults reported barriers more often, and reported some unique barriers relating to language and culture issues. The findings contribute to developing targeted PA programs for older Caucasian and Chinese adults.